1998
DOI: 10.1103/physreva.58.3134
|View full text |Cite
|
Sign up to set email alerts
|

Bose-Einstein condensation in a two-dimensional, trapped, interacting gas

Abstract: We study Bose-Einstein condensation phenomenon in a two-dimensional (2D) system of bosons subjected to an harmonic oscillator type confining potential. The interaction among the 2D bosons is described by a delta-function in configuration space. Solving the Gross-Pitaevskii equation within the two-fluid model we calculate the condensate fraction, ground state energy, and specific heat of the system. Our results indicate that interacting bosons have similar behavior to those of an ideal system for weak interacti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
50
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 23 publications
8
50
0
Order By: Relevance
“…The choice of g is an issue on which there has not been unanimous opinion in the recent papers [12,13,14,15,16,17,18] on this subject. We shall prove that a right choice is g = | ln(ρa 2 )| −1 wherē ρ is a mean density that will be defined more precisely below.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of g is an issue on which there has not been unanimous opinion in the recent papers [12,13,14,15,16,17,18] on this subject. We shall prove that a right choice is g = | ln(ρa 2 )| −1 wherē ρ is a mean density that will be defined more precisely below.…”
Section: Introductionmentioning
confidence: 99%
“…[4]. The results also correlate with the analysis of trapped weakly interacting bosons in two dimensions [21] and with the Hartree-Fock-Bogoliubov treatment of a quasi-two-dimensional trapped Bose system [22]. One should note that a harmonically trapped system in D dimensions effectively corresponds (in the semiclassical approach) to an ideal system in a 2D-dimensional rigid box, cf.…”
Section: Numerical Results and Discussionmentioning
confidence: 49%
“…They have concluded that two regimes can be realized: a true condensate and a quasicondensate with fluctuating phase. In the mean field approximation the properties of such a system have been studied by Bayindir and Tanatar [11]. They demonstrate the similarity in thermodynamic behavior of ideal 2D Bose systems in a harmonic trap and those with weak interactions and a finite number of the particles.…”
Section: Introductionmentioning
confidence: 99%